Seguimiento Al Proceso De Pagos A Proveedores De La Dirección Distrital 09d11 Alfredo Baquerizo Moreno - Simón Bolívar - Educación - Ramos Morales, Jaime Joel (2018)
The entities of the Public Sector have the purpose of providing a service of a character social and free, its main purpose is the benefit for all its inhabitants as establishes the Magna Carta, seek the development of a sovereign, free and democratic country, being these public services of free access for all their community, having these groups rights to assess the efficiency and effectiveness with which their economic resources are managed and humans. The Public Administration according to article 227 of the Constitution of the Republic of Ecuador of October 2008 is governed by the principles of effectiveness, efficiency, quality, hierarchy, deconcentration, decentralization, coordination, participation, planning, transparency and evaluation. In Ecuador, Education is a fundamental right constituted that provides free education to all social statements, on February 1, 2014 according to agreement 0015-14 The provincial and Hispanic bilingual education directorates are definitively closed and the Administrative Units - District Departments of Education that will be divided into Zonal Coordinations in order to provide a quality service and warmth to the educational community according to the canton where they are located, the same as they cover different circuits.